Gender Equality in Surah An-Nisa’ Verse 32 Through Paul Ricoeur’s Hermeneutical Analysis - M. Ali Hafidz; Bymmas Subangga (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to reveal the meaning of gender equality in Qur’anic Surah An-Nisā’ verse 32 through Paul Ricoeur’s hermeneutical approach, particularly the concepts of distanciation, hermeneutics of suspicion, and appropriation. This research employs a qualitative method with a descriptive-analytical library research design. Primary sources include Surah An-Nisā’ verse 32, classical Qur’anic commentaries, contemporary tafsir works, and Paul Ricoeur’s major writings. The analysis was conducted through three stages: structural-linguistic analysis, deconstruction of patriarchal bias, and reconstruction of emancipatory meaning. The findings demonstrate that the verse's grammatical structure employs parallel active forms, iktasabū and iktasabna, which position both men and women as equal active agents. Patriarchal tendencies found in classical interpretations are influenced by socio-cultural ideologies of the exegetes rather than by the Qur’anic text itself. Through Ricoeur’s hermeneutics, the verse is understood as possessing a surplus of meaning that transcends its historical context and promotes justice, equality, and recognition of women’s existence. This study confirms that Ricoeur’s hermeneutics is highly relevant to contemporary Qur’anic interpretation, helping construct a more critical, humanistic, and emancipatory reading of gender issues